Association between endodontic conditions and the relationship of upper posterior teeth and the thickening of the maxillary sinus mucosa. A study using cone beam computerized tomography - C. dos Santos, Andrey Junior; I. Kussaba, Isabela; V. Iwaki, Lilian Cristina; C. da Silva, Mariliani (Brazilian Journal of Health and Biomedical Sciences, 2024)
Introduction: Sinus mucosal thickness and maxillary sinusitis can be caused by several predisposing factors. Some studies indicate that sinusitis can be of odontogenic origin and that this condition is responsible for 10 to 12% of maxillary sinusitis. Objective: To assess the odontogenic conditions of the maxillary posterior teeth and their proximity to the maxillary sinus (SM) and correlate these factors with the mucosal thickness of the SM, using cone beam computed tomography images. Methodology and resources: CBCT images of 393 patients aged between 18 and 75 years were analyzed, noting aspects such as the presence of root canal fillings, periapical lesions, and the contact of the roots of the maxillary posterior teeth with the floor of the SM. Results and discussion: All results are presented as odds ratios (OR) and 95% confidence intervals (CIs). Statistically significant differences (p<0.001) were found among the variables studied, and the probability of thickness of the MS mucosa is greater in men (1.73%), 7.27% when periapical lesions are present and 2.03% in the presence of endodontic treatment. Conclusion: We conclude that periapical lesions, root canal filling and proximity of the dental roots to the floor of the maxillary sinus interfere with the appearance of sinus mucosal thickness.